The prognostic nutritional index represents a novel inflammation-nutrition-based prognostic factor for nasopharyngeal carcinoma - Jiang, Yan-Ming; Huang, Shi-Ting; Pan, Xin-Bin; Ma, Jia-Lin; Zhu, Xiao-Dong (Frontiers in Nutrition, 2023)
Purpose: This study explored the relationship between the prognostic nutritional index (PNI) and overall survival rate (OS) of patients with nasopharyngeal carcinoma (NPC) and established and validated an effective nomogram to predict clinical outcomes. Methods: A total of 618 patients with newly diagnosed locoregionally advanced NPC were enrolled and divided into training and validation cohorts at a 2:1 ratio based on random numbers. OS was the primary endpoint. A nomogram was established based on the results of multivariate analysis. The Harrell concordance index (C-index), area under the receiver operator characteristic curve (AUC), and decision curve analysis (DCA) were used to assess the predictive power and clinical utility of the nomogram and were compared to the current 8th edition of the International Union Against Cancer/American Joint Committee UICC/AJCC staging system. Results: The PNI cutoff value was 48.1. In the univariate analysis, age (P<0.001), T-stage (P<0.001), N-stage(P=0.036), tumor stage (P<0.001), PNI (P= 0.001), lymphocyte-neutrophil ratio (NLR, P=0.002), and lactate dehydrogenase (LDH, P=0.009) were significantly associated with OS, In the multivariate analysis, age (P<0.001), T-stage (P<0.001), N-stage(P=0.02), LDH (P=0.032), and PNI(P=0.006) were significantly associated with OS. The C-index of the nomogram was 0.702 (95% confidence interval [CI]: 0.653–0.751). The Akaike information criterion (AIC) value of the nomogram for OS was 1142.538. The C-index of the TNM staging system was 0.647 (95% CI, 0.594–0.70) and the AIC was 1163.698. The C-index, DCA, and AUC of the nomogram demonstrated its clinical value and higher overall net benefit compared to the eighth edition of the TNM staging system. Conclusions: The PNI represents a novel inflammation-nutrition-based prognostic factor for patients with NPC. The proposed nomogram contains the PNI and LDH, resulting in a more accurate prognostic prediction than the current staging system for patients with NPC.